The Effect Of Sugar And Jelly Concentration On The Quality Of Young Coconut Pudding (Cocos nucifera L.) (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2024)
Oil plants (Cocos nucifera L.) is a versatile plant or plants that have a steeper economic value of all parts of the coconut tree can be the benefits for human needs. False coconut oil is a processed product made from young coconut meat coconut pudding manufacture in modern done through the stages are quite complicated and costly, so that only done by large industries. affect factors on fermentation needs to be optimized to result in qualified young coconut pudding the purpose of this study was to determine influence concentration of sugar and agar-agar to quality coconut pudding in addition to knowing the most permanent treatment that can produce the highest quality coconut pudding the hypothesis of this study. Presumably the influence concentration of sugar and agar-agar to the quality of pudding coconut. And affect the level of consumer preferences. The method used is an experimental research by using a completely randomized design (RAL), which consists of two factors, namely: Concentrations of sugar and gelatin with 300 gram 400 gram 500 gram while the factors gelatin with composition 7 g, 14 g, 21 g. While the variable that is used to measure the level of preference is the color flavor aroma and texture. Variables were measured in this study is using composition test by testing the level of preference are: color, taste, aroma, and texture. Using a scoring scale test method (numbering) commonly in use No. 1-5 and panelists in use totaled 15 0rang representing consumers the results of composition test of the level of preference of color, flavor, aroma, and texture of pudding meat fruit coconut based assessment best treatment that is adjusted from public view representing 15 people panelists then be in concluded that treatment in consider best is in treatment ( GPI Aa2).